2021
DOI: 10.1002/ccr3.4537
|View full text |Cite
|
Sign up to set email alerts
|

Oral manifestations and dental care management of a young patient with lymphangioma of the tongue: A case report

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…One of these studies, Ozeki et al, 17 included adults and children but only the pediatric data was extracted for this review. Ten retrospective case series [19][20][21][22][23][24][25][26][27][28] and five individual case reports [29][30][31][32][33] of sirolimus use in cervicofacial LMs were also included; these are summarized in Table II. Assessment of risk of bias for all included studies is shown in Table III.…”
Section: Search Resultsmentioning
confidence: 99%
“…One of these studies, Ozeki et al, 17 included adults and children but only the pediatric data was extracted for this review. Ten retrospective case series [19][20][21][22][23][24][25][26][27][28] and five individual case reports [29][30][31][32][33] of sirolimus use in cervicofacial LMs were also included; these are summarized in Table II. Assessment of risk of bias for all included studies is shown in Table III.…”
Section: Search Resultsmentioning
confidence: 99%
“…Zhang reported to use a reduced starting dose in neonates (0.5 mg/m 2 ). Other starting doses were 1–2 mg per day [ 31 ], 0.1 mg/kg per day [ 35 ], 0.05 mg/kg twice daily [ 16 ], 0.6 mg/m 2 per twice daily dose [ 33 ], 0.07 mg/kg twice daily [ 18 ], 0.4–0.8 mg/m 2 twice daily [ 20 ] or in two fractions [ 27 ], and 1.5 mg/kg/day administered in two divided daily doses [ 37 ]. In five publications, the initial dose of sirolimus was not reported [ 12 , 14 , 15 , 22 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…In one study each, 3.5–6 ng/mL [ 30 ], 4–8 ng/mL [ 21 ], 4–10 ng/mL [ 38 ], 4–13 ng/mL [ 36 ], 5–12 ng/mL [ 33 ], 10–12 ng/mL [ 27 ], 10–13 ng/mL [ 19 ] and 12–20 ng/mL [ 35 ] were the target concentrations. Eight studies did not report the target blood level of sirolimus [ 12 , 13 , 15 , 18 , 22 , 29 , 32 , 37 ]. Not in all studies the planned target trough level for sirolimus was achieved [ 14 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lymphatic endothelium reveals positive staining for marker D2-40. Small blood vessels positively stained for CD31 are also present in the lamina propria [9,14,15]. Prenatal chromosomal analysis including 13, 18, 21, X, and Y may reveal the increased possibility for lymphangioma formation.…”
Section: Discussionmentioning
confidence: 99%